Reaching for the stars: Australian firms and the global productivity frontier - Dan Andrews; Jonathan Hambur; David Hansell; Angus Wheeler (The Australian Government, The Treasury, 2022)
A feature of the recent global slowdown in productivity growth is that progress at the technological frontier has remained strong, while the gap between firms at the global frontier and other 'laggards' within an industry has grown. This growing gap reflects the fact that laggard firms now seem to be slower to adopt cutting-edge technologies and processes, and catch-up to the global frontier than they were previously. However, little is known about whether these patterns hold true for Australia. We exploit a novel dataset merging international microdata from OECD-Orbis with Australian microdata from BLADE. Consistent with overseas evidence, we find that the gap between global frontier firms and Australian firms has grown over time in the non-resource, non-financial market sector. Moreover, Australian firms catch up to the global frontier more slowly than previously, suggesting slower adoption of cutting-edge technologies and processes. The slowdown has been more notable in industries with declining measures of dynamism and competitive pressures, suggesting the slowdown may reflect weaker incentives and imperatives for firms to improve. This suggests that policies to address barriers to business dynamism and competitive pressures can improve Australia's productivity performance, by increasing incentives for firms to adopt, innovate and improve.
Keywords: C23; C55; D22; D30; E23; E24; 330; productivity; dispersion; firm-level; BLADE; frontier